Prototipe Sistem ETCS Berbasis Arduino Uno Pada Kereta Light Rail Transit Sumatera Selatan - Ikhsan Anugrah; Endah Fitriani (ELECTRON Jurnal Ilmiah Teknik Elektro, 2025)
This study aims to develop a simulation of the ETCS (European Train Control System) system based on Arduino Uno for Light Rail Transit (LRT) trains in South Sumatra. The main focus of the study is on the automation of train operation, the identification of disturbing objects, and handling potential errors in programming. Tests and analysis show that an active Ultrasonic Sensor allows the train to stop if there is an object blocking it in front of it at a distance of less than 20 cm. The TCS200 color sensor plays an important role in activating the Servo so that the crossbar can be active so that the train can run again. The colored signal LED lights become markers, the red LED indicates the down bar and the green LED lights indicates the up bar. The LCD is here to display the destination of the train station which is located on the side of the train body. The buzzer is a marker for the train stopping and the timer is set to 5 seconds per each train stopping at the station. Of course there are drawbacks, namely that there are no automatic doors when the train stops at the station and the station is relatively quiet and there are no additional accessories and lights at the station